Development of census-GIS methodology in Pakistan - Syed Nawaz ul Huda,; Burke, Farkhunda; Ghazi Salahuddin,; Imran Ahmad,; Mazhar Jamal, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Census, which is generally conducted at decennial intervals in Pakistan, plays an essential role for collection of wide range of data. It is of prime importance for national planning as it is the main source for the study of various aspects of population, who are the beneficiaries/sufferers of any governmental policies. Manual methods of census conduction being cumbersome and erroneous, has become obsolete and outdated and is being increasingly replaced by automated methods, notably Census GIS. The objective of this paper is to present a model for the implementation of GIs for census enumeration, in order to overcome the inordinate delay in the last census in Pakistan, as census is the basis for streamlined and fool proof national, local and regional planning and disaster management.